A new family of thermoplastic photoluminescence polymers. Issue 40 (26th September 2016) - Ru, Yue; Zhang, Xiaohong; Song, Wenbo; Liu, Zhenjie; Feng, Huasheng; Wang, Bin; Guo, Mingming; Wang, Xiang; Luo, Chunxia; Yang, Wantai; Li, Yongfang; Qiao, Jinliang
Abstract : In order to overcome the drawback of traditional photoluminescence materials, which are usually opaque, expensive and non-thermoplastic, a new family of photoluminescence alternate copolymers made from maleic anhydride and different olefin derivatives with very low cost have been developed and are reported in this paper. Abstract : In order to overcome the drawback of traditional photoluminescence materials, which are usually opaque, expensive and non-thermoplastic, a new family of photoluminescence alternate copolymers made from maleic anhydride and different olefin derivatives with very low cost have been developed and are reported in this paper. The new photoluminescence polymers are all transparent-thermoplastic fluorescence polymers and the photoluminescence polymers made from maleic anhydride and styrene or its derivatives are all phosphorescence polymers, which are the first reported family of phosphorescence polymers without traditional luminous groups. A transparent and thermoplastic photoluminescence material with low cost has been a dream of both academia and industry for many years because it is an extremely important material for agriculture, LEDs, organic optoelectronics, anti-counterfeiting materials, coatings, illuminants, displays and many other areas; therefore, it is believed that this new family of photoluminescence polymers can contribute greatly to the sustainable development of our society.